A Review On Kumkumadya Oil - Konde, Apurva Haridas; Chikurte, Sharada N (International Research Journal of Ayurveda & Yoga, 2021)
The aim of Ayurved is to protect health of healthy and eliminate diseases. Due to imbalance diet, increased pollution, stress, hormonal imbalance etc. skin problems are prominent nowadays. Apart from skin problems beauty has its own importance all the time. Herbal formulation like Kumkumadya oil/ tailam is one of the skin remedy for normal skin to be continued with glow and fairness. It is also for Nilika, pidaka and Vanga. It improves skin complexion and texture.Oil is one of the aushadha Kalpana comes under the Sneha Kalpaa. Dravya used to processed Sneha, increases the efficacy of Sneha.